ANALISIS KEBIJAKAN BAZNAS TENTANG IBNU SABIL SEBAGAI MUSTAHIK ZAKAT - Setiawan, Adi; Putra, Trisno Wardy; Hariyadi, Risky (Jurnal Ar-Ribh, 2020)
The scholars differed in defining and establishing ibn sabil as mustahik zakat. There are certain qualifying requirements for mustahik ibnu sabil. Likewise, the National Zakat Agency has qualified the mustahik ibnu sabil group in several qualifications. This study uses qualitative methods, namely methods that will produce descriptive data, in the form of written or spoken words. While the data collection techniques used are interview techniques (interviews), and documentation. From the results of this study it can be found that basically the BAZNAS policy regarding Ibn Sabil as Mustahik Zakat is in accordance with the concept of Ibn Sabil as Mustahik Zakat according to the Al-Quran (QS. At-Taubah: 60).